2022
DOI: 10.34172/jcvtr.2022.30
|View full text |Cite
|
Sign up to set email alerts
|

Value of myocardial deformation parameters for detecting significant coronary artery disease

Abstract: Introduction: The study aimed to evaluate the diagnostic value of global and regional myocardial deformation parameters derived from two-dimensional speckle-tracking echocardiography to detect functionally significant coronary artery stenosis. Methods: Dobutamine stress echocardiography and cardiac magnetic resonance myocardial perfusion imaging (CMR-MPI) were performed on 145 patients with a moderate and high probability of coronary artery disease (CAD) and LVEF≥55%. Significant CAD was defined as>50% sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This enhances the formation of erythrocytes in the kidney, affects hemodynamics, and increases hemoglobin content, number of erythrocytes and hematocrit content. Hematocrit is related to blood viscosity which reduces the effective perfusion of the cardiovascular system, aggravates myocardial ischemia and hypoxia, thereby forming a vicious circle [17]. It has been shown that amiodarone improves hemodynamics in CHD patients with arrhythmia [18].…”
Section: Discussionmentioning
confidence: 99%
“…This enhances the formation of erythrocytes in the kidney, affects hemodynamics, and increases hemoglobin content, number of erythrocytes and hematocrit content. Hematocrit is related to blood viscosity which reduces the effective perfusion of the cardiovascular system, aggravates myocardial ischemia and hypoxia, thereby forming a vicious circle [17]. It has been shown that amiodarone improves hemodynamics in CHD patients with arrhythmia [18].…”
Section: Discussionmentioning
confidence: 99%